Effect of obesity on sperm retrieval outcome and reproductive hormone levels in Japanese azoospermic men with and without Klinefelter syndrome. (21st September 2016) - Iwatsuki, S.; Sasaki, S.; Taguchi, K.; Hamakawa, T.; Mizuno, K.; Okada, A.; Kubota, Y.; Umemoto, Y.; Hayashi, Y.; Yasui, T.
Summary: Obesity is reported to have adverse effects on semen quality and the endocrine system. In this study, we evaluated the effect of obesity on sperm retrieval outcome and reproductive hormone levels in Japanese men with non‐obstructive azoospermia (NOA). This study is based on the clinical records of 217 men [172 with a 46, XY karyotype, 45 with Klinefelter syndrome (KS)] with NOA who underwent microdissection testicular sperm extraction at Nagoya City University Hospital between January 2004 and December 2014. Body mass index (BMI) and serum levels of luteinizing hormone (LH), follicle‐stimulating hormone (FSH), and total testosterone (TT) were measured in all patients. In a subset of patients, bioavailable testosterone (cBAT) also was calculated. Values were evaluated separately in patients with and without KS. Sperm retrieval rates (SRRs) in 46, XY men with a BMI <25 kg/m 2 and ≥25 kg/m 2 were 29.3% and 18.4%, respectively ( p = 0.142), while SRRs in KS men with a BMI <25 kg/m 2 and ≥25 kg/m 2 were 25.0% and 35.3%, respectively ( p = 0.460). TT level in men with a BMI ≥25 kg/m 2 was lower than that in men with a BMI <25 kg/m 2, regardless of KS status. According to Pearson product‐moment correlation coefficients, TT and cBAT levels tended to have negative correlations with BMI; however, statistical significance was observed only for TT level in 46, XY men ( r = 0.340, p < 0.001). LH and FSH levels were negatively correlated with BMI in KS men ( r = −0.466, p = 0.001 and r = −0.647, p < 0.001, respectively), but not in 46, XY men. These results suggest that obesity may be irrelevant to sperm retrieval outcome in patients with NOA. The negative correlations between gonadotropins and BMI in patients with KS suggest an underlying suppressive effect on gonadotropin excretion, which is distinctive in obese patients with KS.